ound Healing Evaluation of Some Herbal Formulations Containing Curcuma Longa and Cynodon Dactylon Extract - Vinod M. Thakare,; R. Y. Chaudhari,; V.R. Patil, (International Journal of Phytomedicine, 2011)
The wound healing effect of herbal cream formulated with Curcuma longa, and Cynodon dactylon embedded in different ointment bases (anionic, cationic and non-ionic) has been evaluated in vivo using the incision, excision and dead space tissue wound models, on Swiss wister rat. Curcuma longa, and Cynodon dactylon was extracted using Pet ether (60-800C ), chloroform, ethanol, methanol and water. The methanolic extract formulated as herbal preparations. The herbal preparations were used to treat wounds inflicted on experimental Swiss wister rat. The wound healing effects of the formulations were compared to that of a standard antibiotic. In all cases, there was a progressive decrease in wound area with time, indicating an efficacy of the formulations in healing the induced wounds. By the 16th day, the formulation containing 100 mg/g of Curcuma longa, and Cynodon dactylon in cationic base showed 100 % healing. The wound areas in the animals treated with the standard antibiotic, showed a 100% healing by the 17 th day, indicating that the plant extract, at that given concentration, had a better wound healing property.